Governing policies and factors affecting the labor market integration of female accompanying spouses - Saurombe, Musawenkosi Donia; Zinatsa, Farirai (Frontiers in Sociology, 2023)
Introduction This study sought to ascertain the macro governing policies and factors that influence the integration of female accompanying spouses in the Free State, into the South African labor market. Methods Utilizing a qualitative approach, thirteen one-on-one interviews, consisting of an initial purposive sample and a subsequent snowball sample, were conducted for data gathering. The study employed thematic analysis to interpret the data. Results The findings revealed that governing policies emerging from South Africa's migration legislation, and factors such as spouse dependence, reinforcement of traditional gender roles, and restrictive employment legislation which forced deskilling of qualifications, mainly impacted the conduct of accompanying spouses concerning the labor market. Discussion This study contributes to the literature on labor market integration (LMI) from an underexplored South-to-South standpoint by delving into the experiences of skilled female migrants in the family migration setting. A neglected facet of Michel Foucault's governmentality theory was used to investigate the labor market assimilation needs of female accompanying spouses. The study's qualitative approach renders the findings much less generalizable than a quantitative inquiry. It is important to note that LMI research is considerably setting-specific, despite some aspects of this study being applicable to other settings in the Global South. South Africa continues to be a pivotal regional hub for migration in the Global South, yet it has a complex migration governance framework that sets up a specific, while broadly exclusionary, macro context for accompanying spouses. This study zones in on issues that could inform more effective family migration policy.